Effect of Footwear Versus Barefoot on Double-Leg Jump-Landing and Jump Height Measures: A Randomized Cross-Over Study - Hébert-Losier, Kim; Boswell-Smith, Caleb; Hanzlíková, Ivana (International journal of sports physical therapy, 2023)
BACKGROUND: Assessing individuals in their own athletic footwear in clinics is common, but can affect movement, performance, and clinical measures. PURPOSE: The aim was to compare overall Landing Error Scoring System (LESS) scores, injury risk categorization, specific LESS errors, and jump heights between habitual athletic footwear and barefoot conditions. STUDY DESIGN: Randomized cross-over laboratory study. METHODS: Eighty healthy individuals (55% male) completed the LESS following standard procedures (i.e., land from a 30-cm box to a distance of 50% of body height and then jump upwards maximally). Participants performed the LESS three times in two randomized conditions: footwear and barefoot. LESS data were extracted from 2D videos to compare group-level mean LESS scores, group-level and individual-level injury risk categorization (5-error threshold), specific landing errors, and jump heights between conditions. RESULTS: LESS scores were significantly greater (0.3 errors, p=0.022) and jump heights were significantly lower (0.6 cm, p=0.029) in footwear than barefoot, but differences were trivial (d = 0.18 and -0.07, respectively) and not clinically meaningful. Although the number of high injury-risk participants was not statistically different at a group level (p=1.000); 27 individuals (33.8%) exhibited a clinically meaningful difference between conditions of one error or more in LESS score, categorization was inconsistent for 16.3% of individuals, and four of the 17 landing errors significantly differed between conditions. CONCLUSION: At a group level, habitual athletic footwear does not meaningfully influence LESS scores, risk categorization, or jump height. At an individual level, footwear can meaningfully affect LESS scores, risk categorization, and alter landing strategies. Use of consistent protocol and footwear is advised for assessing movement patterns and injury risk from the LESS given the unknown predictive value of this test barefoot. LEVEL OF EVIDENCE: Level 3.©The Author(s).
Keywords: knee; biomechanics; screening; Anterior Cruciate Ligament